A study of clinical profile and management of perforation peritonitis in a tertiary health centre located in Central India - Jain, Neeraj Kumar; Jain, Manjari Goel; Maini, Sunil; Khobragade, Vicky (International Surgery Journal, 2017)
Background: Perforation peritonitis is the most common surgical emergency in India. The spectrum of etiology of perforation in tropical countries continues to be different from its Western counterpart. The objective of the study was to highlight the spectrum of perforation peritonitis as encountered by us at RKDF medical college and research centre, Bhopal, Madhya Pradesh, India. Methods: Our prospective observational study was conducted at Department of General Surgery, R.K.D.F. Medical College and Research Centre, Bhopal, Madhya Pradesh, India during period of August 2013 to August 2015. Total 110 cases of perforation peritonitis were included. Patient detailed history, symptoms, sign, blood investigation finding, cause of perforation, site of perforation, type of surgery, post-operative complications and mortality were assessed and result were compared with other studies. Results: The most common cause of perforation in our series was perforated peptic ulcer (52 cases) followed by typhoid fever perforation (21 cases), appendicular (16 cases) and tuberculosis (11 cases). Despite delay in seeking medical treatment, the overall mortality (16.36%) was comparable with other published series though the overall morbidity (63%) was unusually high. Conclusions: In contrast to western literature, where lower gastrointestinal tract perforations predominate, upper gastrointestinal tract perforations constitute the majority of cases in Central India.